2004
DOI: 10.1095/biolreprod.103.023739
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Antral Follicular Wave Dynamics and Accompanying Endocrine Changes in Cyclic and Seasonally Anestrous Ewes Treated with Exogenous Ovine Follicle-Stimulating Hormone During the Inter-Wave Interval1

Abstract: In the ewe, ovarian follicular waves emerge every 4 to 5 days and are preceded by a peak in FSH secretion. It is unclear whether large antral follicle(s) in a wave suppress the growth of other smaller follicles during the inter-wave interval, as is seen in cattle. In this study, anestrous (n = 6; experiment 1) and cyclic (n = 5; experiment 2) Western white face ewes were given ovine FSH (oFSH) (0.5 microg/kg; two s.c. injections, 8 h apart) during the growth phase (based on ultrasonography) of a follicular wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 49 publications
(96 reference statements)
5
53
1
2
Order By: Relevance
“…While some authors have postulated the existence of follicular dominance especially during first and final follicular waves [29,30], others are still dispute this [31,32]. In ewes, follicular waves have been frequently found to emerge in the presence of growing ovulatory-sized follicles from a previous wave [33,34] and large (presumably dominant) follicles do not inhibit equine chorionic gonadotropin (eCG)-induced growth of other follicles [31].…”
Section: Discussionmentioning
confidence: 99%
“…While some authors have postulated the existence of follicular dominance especially during first and final follicular waves [29,30], others are still dispute this [31,32]. In ewes, follicular waves have been frequently found to emerge in the presence of growing ovulatory-sized follicles from a previous wave [33,34] and large (presumably dominant) follicles do not inhibit equine chorionic gonadotropin (eCG)-induced growth of other follicles [31].…”
Section: Discussionmentioning
confidence: 99%
“…The oFSH for injection was prepared in saline with 0.05% BSA (w/v; Sigma Chemical Co., St. Louis, MO) and 50% polyvinylpyrrolidone (w/v; Sigma) [12].…”
Section: Hormone Preparationmentioning
confidence: 99%
“…Treatment of ewes with a superovulatory dose of FSH results in increased numbers of follicles growing to an ovulatory diameter [16][17][18][19]; however, the effects of changes in the amplitude of FSH peaks within a physiological range have not been tested. In a recent study from our laboratory [12], we demonstrated that the presence of the largest follicle of a wave induced by a treatment with ovine FSH (oFSH) did not postpone the occurrence of the next endogenous FSH peak. However, it is not known whether an increase in the frequency of FSH peaks, using repeated injections of FSH, would disrupt the rhythmic occurrence of endogenous FSH peaks and the regular emergence of follicular waves.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations